2017
DOI: 10.1186/s12870-017-1051-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief temperature stress during reproductive stages alters meiotic recombination and somatic mutation rates in the progeny of Arabidopsis

Abstract: BackgroundPlants exposed to environmental stresses draw upon many genetic and epigenetic strategies, with the former sometimes modulated by the latter. This can help the plant, and its immediate progeny, at least, to better endure the stress. Some evidence has led to proposals that (epi) genetic changes can be both selective and sustainably heritable, while other evidence suggests that changes are effectively stochastic, and important only because they induce genetic variation. One type of stress with an argua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 58 publications
(94 reference statements)
0
24
0
1
Order By: Relevance
“…In other genomic regions, however, the meiotic cross-over rate appears unaffected or even increased, indicating that heat does not merely affect the overall genome-wide cross-over level, but instead causes a spatial redistribution of cross-over events along the chromosome. The overall effect of varying temperatures on meiotic crossover rate and distribution in Arabidopsis was recently investigated by several groups 16,18,32 . These studies revealed that heat increases the overall recombination rate in male meiosis, and that the extra crossovers under heat are formed via the class I interference-sensitive pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In other genomic regions, however, the meiotic cross-over rate appears unaffected or even increased, indicating that heat does not merely affect the overall genome-wide cross-over level, but instead causes a spatial redistribution of cross-over events along the chromosome. The overall effect of varying temperatures on meiotic crossover rate and distribution in Arabidopsis was recently investigated by several groups 16,18,32 . These studies revealed that heat increases the overall recombination rate in male meiosis, and that the extra crossovers under heat are formed via the class I interference-sensitive pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond sequence-related effects, recombination can also be modulated by epigenetic factors, as observed in centromeric regions (N. A. Yelina et al 2012, and by environmental conditions (Phillips et al 2015;Saini et al 2017;Zhang et al 2017).…”
Section: Genetic Control Of Recombination Ratementioning
confidence: 99%
“…In flowering plants, environmental factors play an important role in the regulation of plant growth and development, and the reproductive phase is typically highly sensitive to temperature stress (Gao et al, 2014;Ohnishi et al, 2010;Saini et al, 2017;Yang et al, 2015a). Complications can include abnormal meiosis (Bita et al, 2011;Draeger and Moore, 2017;Ohnishi et al, 2010;Yang et al, 2015a); accelerated pollen development and increased pollen abortion (Higuchi et al, 1998;Shen et al, 1999); accelerated flower bud development, resulting in a hastening of flowering time (Rodrigo and Herrero, 2002); reduced pollen germination for underdeveloped pistils (Hedhly et al, 2004;Koubouris et al, 2009;Pham et al, 2015); faster pollen tube growth in the style (Hedhly et al, 2004;Xu and Xu, 2014); inhibition of pollen tube elongation (Zhang et al, 2018); reduction in the number of pollen tubes (Radi cevi c et al, 2016); and reduction in the percentage of the style traversed by the pollen tube (Gao et al, 2014;Koubouris et al, 2009;Pham et al, 2015;Song and Chen, 2018), all of which can result in low fruit set.…”
mentioning
confidence: 99%